(untitled) (Research, Society and Development, 2022)
Preventive medicine is a fundamental area of ​​the Unified Health System, with coverage in national programs, in the high complexity of its actions, low technological density. This research aimed to analyze the scientific evidence regarding the importance of preventive medicine in society, from the beginning of the SUS to the present pandemic context. This is an integrative literature review carried out in the LILACS and SCIELO databases, with the inclusion of studies from the last five years. Screening processes and early diagnosis are crucial to enable prompt treatment, prevent disease progression and reduce morbidity and mortality. Health technologies are essential for advancing and improving the quality of care provided to patients, implementations of virtual consultations should be used more frequently as a clinical communication tool between health professionals and patients. It was found that medicine stands out in the fight against the pandemic, and that preventive medicine is a fundamental strategy and action to reduce infection and morbidity and mortality rates, promoting comprehensive care to the client with a focus on prevention, health promotion and patient recovery. in all your assistance needs with respect to the principles and guidelines of the SUS for the patient.